IMPLEMENTASI NILAI-NILAI SOCIAL STUDIES DALAM KURIKULUM 2013 DI SMK YADIKA 5 TANGERANG SELATAN - Pebi Ayu Indiputri; Suswandari; Hari Naredi (Prosiding Seminar Nasional Berseri, 2020)
The purpose of this study was to determine the characteristics of organizing Social Studies at the Vocational School level, to know the value that Social Studies learning can be implemented in the daily lives of students, to know the process of developing and strengthening the values â€‹â€‹of Social Studies for SMK students. This type of research uses a qualitative approach with the case study method. This study uses data collection techniques such as observation, interviews and documentation. The results of this study indicate that: (1) Learning social studies in vocational schools emphasizes the preparation of students into the world of work where students must be able to understand deeply about concepts in the life of a pluralistic society. Social studies in the 2013 curriculum at SMK Yadika 5 were developed based on social science disciplines that contained material on Indonesian History and Pancasila and Citizenship Education. (2) Teachers instill the basic values â€‹â€‹of social studies that apply in the community in the form of building the ability to adapt, have a sense of responsibility, have values â€‹â€‹of honesty, tolerance and are able to work together. The conclusion of this study is that both the teacher and all the residents of the Yadika 5 Vocational School have sought the values â€‹â€‹of social studies into students so that they can become students’ characteristics.